A defesa na investigação policial como garantia da dignidade humana na Constituição Federal de 1988: da Súmula Vinculante n. 14/2009 ao Provimento n. 188/2018 da OAB - Vilhena, Jaciléia Rocha de (2024)
In this dissertation, the right to defense in police investigation is analyzed, in the light of human dignity, as a foundation of the State, under the terms of art. 1, III, of the Brazilian Federal Constitution of 1988, and the rights and guarantees set out in art. 5º, LV, LIV and LVII, of the Charter. Continuously, doctrinal aspects of the applicability of these rights are investigated, in addition to the current confrontation of the issue in the normative field, through Binding Precedent n. 14/2009 and Provision no. 188/2018 from OAB. It starts from the premise that human dignity has shed light on all of humanity, supported by the doctrine of humanist capitalism, which announces its bases in the quantum order of law, through the consubstantiality between positive law and human rights – represented by dignity – and by legal realism, which shape the singularity of law in itself. To this end, we analyze what systems are and how the investigation and the person are seen according to each society, the historical bases of the police investigation and the consolidation of this instrument in the Middle Ages, under the influence of canon law. With an emphasis on the Enlightenment, it addresses how the ideas generated at this historical moment came about, especially with regard to the subsequent consolidation of human rights, established after the great Revolutions, and in modernity, due to the impact of the Great Wars, which culminated in the Universal Declaration of Human Rights in 1948 and other international documents imbued with the same protective bias towards human beings. Based on some specific milestones, the trajectory in Brazil of the formation of the police investigation as a method/instrument used by the State and its multiple aspects involving the applicability and/or mitigation of rights and constitutional guarantees applicable to the matter is traced, to reach to the current legal conformation, to the Binding Precedent n. 14/2009 and Provision no. 188/2018 of OAB, as a pragmatic link in the exercise of proactive technical defense in Brazil starting from the state investigation